Beyond the Streets: Rethinking Legal Protection for Exploited Street Children in Indonesia - Musofiana, Ida; Ahmed Kheir Osman (Jurnal Ius Constituendum, 2025)
This study investigates the urgency of providing legal protection for street children who are victims of exploitation amid the increasing number of reported cases and weak law enforcement responses. Employing a normative juridical method with a descriptive–analytical approach, the research integrates primary and secondary legal materials to evaluate the effectiveness of existing protection mechanisms. The findings reveal that poverty, limited social supervision, and the absence of deterrent sanctions are the dominant factors driving child exploitation. The consequences are multidimensional, adversely affecting the children’s physical health, education, psychological stability, and long-term socioeconomic prospects. The novelty of this research lies in its interdisciplinary integration of legal, social, economic, educational, and health perspectives to formulate a responsive and applicable model of protection. The study concludes that combating the exploitation of street children requires more than normative regulations; it demands a coordinated cross-sectoral framework involving legal institutions, social welfare agencies, and community participation to ensure effective and sustainable protection.